Type 2 Immune Mechanisms in Carbon Nanotube-Induced Lung Fibrosis - Dong, Jie; Ma, Qiang (Frontiers in Immunology, 2018)
T helper (Th) 2-dependent type 2 immune pathways have been recognized as an important driver for the development of fibrosis. Upon stimulation, activated Th2 immune cells and type 2 cytokines interact with inflammatory and tissue repair functions to stimulate an overzealous reparative response to tissue damage, leading to organ fibrosis and destruction. In this connection, type 2 pathways are activated by a variety of insults and pathological conditions to modulate the response. Carbon nanotubes (CNTs) are nanomaterials with a wide range of applications. However, pulmonary exposure to CNTs causes a number of pathologic outcomes in animal lungs, dominated by inflammation and fibrosis. These findings, alongside the rapidly expanding production and commercialization of CNTs and CNT-containing materials in recent years, have raised concerns on the health risk of CNT exposure in humans. The CNT-induced pulmonary fibrotic lesions resemble those of human fibrotic lung diseases, such as idiopathic pulmonary fibrosis (IPF) and pneumoconiosis, to a certain extent with regard to disease development and pathological features. In fibrotic scenarios, immune cells are activated including varying immune pathways, ranging from innate immune cell activation to autoimmune disease. These events often precede and/or accompany the occurrence of fibrosis. Upon CNT exposure, significant induction and activation of Th2 cells and type 2 cytokines in the lungs are observed. Moreover, type 2 pathways are shown to play important roles in promoting CNT-induced lung fibrosis by producing type 2 pro-fibrotic factors and inducing the reparative phenotypes of macrophages in response to CNTs. In light of the vastly increased demand for nanosafety and the apparent induction and multiple roles of type 2 immune pathways in lung fibrosis, we review the current literature on CNT-induced lung fibrosis, with a focus on the induction and activation of type 2 responses by CNTs and the stimulating function of type 2 signaling on pulmonary fibrosis development. These analyses provide new insights into the mechanistic understanding of CNT-induced lung fibrosis, as well as the potential of using type 2 responses as a monitoring target and therapeutic strategy for human fibrotic lung disease.